THE EFFECTIVENESS OF BOOKLET MEDIA IN EFFORTS IO IMPROVE KNOWLEDGE AND ATTITUDE TO PREVENT CHRONIC ENERGY DEFICIENCY IN PREGNANT WOMEN IN TULUNGAGUNG - D.K, Indah; isnaeni, Ely; Dewi Rokhanawati; Farida Kartini (Nursing Sciences Journal, 2025)
The prevalence of Chronic Energy Deficiency (CED) among pregnant women globally reaches 35–75% (WHO, 2017), and around 40% of maternal deaths in developing countries are associated with this condition. In Indonesia, studies conducted in 2017–2018 reported a CED prevalence of 17.3% and anemia in 48.9% of pregnant women. The 2021 National Health Survey (Riskesdas) reported that the risk of CED in East Java was 29.8%, higher than the national rate of 28%. This study aimed to determine the knowledge and attitudes of pregnant women regarding CED before and after the intervention, as well as to analyze the effect of the “Prevent CED” booklet on first-trimester pregnant women at Kedungwaru Public Health Center in 2024. The study used a pre-experimental One Group Pre-Test Post-Test design with total sampling, involving 25 respondents—second-trimester pregnant women who were registered, received services at the health center, and provided informed consent. Data were analyzed using the Wilcoxon Signed Rank test. The results showed a p-value of 0.003 (<0.05), indicating a significant effect of the booklet on improving the knowledge and attitudes of pregnant women regarding CED prevention. It is recommended that first-trimester pregnant women read the booklet to enhance understanding and prevent CED during pregnancy.